2018
DOI: 10.1136/jclinpath-2018-205227
|View full text |Cite
|
Sign up to set email alerts
|

Essential thrombocythaemia with mutation inMPL: clinicopathological correlation and comparison withJAK2V617F-mutated andCALR-mutated genotypes

Abstract: and ET genotypes share clinical and histological characteristics. In contrast to genotype, features of prefibrotic myelofibrosis are uncommon in -mutated ET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…These conditions notwithstanding, we have documented, even prior to central pathology review, a significantly higher rate of fibrotic progression in MPL -mutated ET compared to patients with other driver mutations. While not all reports are consistent in this regard 14 , our data remain aligned with the majority of large scale, mature studies on the subject 8 , 9 . After central pathology review, the similar rates of fibrotic progression between morphologically confirmed MPL -mutated ET and those reassigned as prefibrotic PMF further suggest the latter to be biologically more akin to PMF.…”
supporting
confidence: 86%
“…These conditions notwithstanding, we have documented, even prior to central pathology review, a significantly higher rate of fibrotic progression in MPL -mutated ET compared to patients with other driver mutations. While not all reports are consistent in this regard 14 , our data remain aligned with the majority of large scale, mature studies on the subject 8 , 9 . After central pathology review, the similar rates of fibrotic progression between morphologically confirmed MPL -mutated ET and those reassigned as prefibrotic PMF further suggest the latter to be biologically more akin to PMF.…”
supporting
confidence: 86%
“…Calreticulin ( CALR ) gene mutations have recently been discovered in about 20%–35% of patients affected by essential thrombocythemia (ET) and primary myelofibrosis (PMF) [26]. An additional percentage of ET patients presents with MPL mutation [27].…”
Section: Digital Pcr In Philadelphia Negative Chronic Myeloprolifementioning
confidence: 99%
“…Due to the lack of effective therapies, able to induce molecular remission in MPN patients, the development of techniques for the detection of MRD has not been heavily pushed. Recently, a new scenario is on the horizon with new targeted therapies available or under development [27].…”
Section: Digital Pcr In Philadelphia Negative Chronic Myeloprolifementioning
confidence: 99%
“…As concluded from the serial revisions of the prognostication models, thrombosis risk may vary according to the mutational status. For instance, the integration of MPL mutations in the revised IPSET model relied on the association of this mutation with older age (a main risk factor for ET prognosis) [ 38 ]. Although MPL -mutated patients share a similar clinical picture with CALR -mutants, the latter group has a lower incidence of thrombosis, especially when compared to JAK2 V617F mutated counterpart (10.5 vs .…”
Section: Risk Factors and Stratification Modelsmentioning
confidence: 99%